2019
DOI: 10.3390/nu11051115
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Tea Regulating Blood Pressure: Evidences and Promises

Abstract: Cardiovascular diseases have overtaken cancers as the number one cause of death. Hypertension is the most dangerous factor linked to deaths caused by cardiovascular diseases. Many researchers have reported that tea has anti-hypertensive effects in animals and humans. The aim of this review is to update the information on the anti-hypertensive effects of tea in human interventions and animal studies, and to summarize the underlying mechanisms, based on ex-vivo tissue and cell culture data. During recent years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 97 publications
2
31
2
Order By: Relevance
“…Camellia sinensis (black tea) gained attention for its polyphenol compounds including epigallocatechin-3-gallate (EGCG), epigallocatechin (EGC), epicatechin-3-gallate (ECG) and epicatechin (EC), which have been reported to have wide range of health promoting effects (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Camellia sinensis (black tea) gained attention for its polyphenol compounds including epigallocatechin-3-gallate (EGCG), epigallocatechin (EGC), epicatechin-3-gallate (ECG) and epicatechin (EC), which have been reported to have wide range of health promoting effects (12) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to estimate the exact amount of nitrate from 750 g nitrate-rich vegetables in the HD and to predict to what extent the NO pathway has contributed to the blood pressure reduction. A number of human intervention trials have shown the antihypertensive effect of green and black tea, possibly related to the polyphenolic compounds (flavonoids) present in tea that possess antioxidative properties ( 46 ). Together with the polyphenol-rich vegetables, the regular consumption of tea in the HD group may also have contributed to a lower BP.…”
Section: Discussionmentioning
confidence: 99%
“…The three major classes of avonoids are avonols, avones and catechins. Studies either in vitro or ex vivo have shown that tea extracts, such as avonoids and its secondary metabolites, may participate in manipulating the smooth muscle relaxation, nitric oxide synthase activity in endothelial cells, vascular in ammation reduction, and renin activity inhibition through its anti-in ammatory and anti-oxidative effects [17,31]. In addition, studies also showed that avonoids and tea catechins can signi cantly improve endothelial function [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Tea is a worldwide popular beverage, and tea consumption has been shown to lead to a reduced risk of cardiovascular disease, hypertension, diabetes, and lung cancer [15][16][17][18]. Twice daily tea consumption at a minimum has been found to be related to a lower risk of COPD [19].…”
Section: Introductionmentioning
confidence: 99%